Difference between revisions of "022 Exam 2 Sample B, Problem 5"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam"> Find the antiderivative of <math>\int \frac{2e^{2x}}{e^2x + 1}\, dx.</math> {| class="mw-collapsible mw-collapsed" style = "text-align:left;" !Foundations...")
 
 
(6 intermediate revisions by the same user not shown)
Line 1: Line 1:
<span class="exam"> Find the antiderivative of <math>\int \frac{2e^{2x}}{e^2x + 1}\, dx.</math>
+
<span class="exam"> Find the antiderivative of <math>\int \frac{2e^{2x}}{e^{2x} + 1}\, dx.</math>
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
Line 22: Line 22:
 
!Step 1: &nbsp;
 
!Step 1: &nbsp;
 
|-
 
|-
|Use a ''u''-substitution with <math style="vertical-align: -8%">u = e^{x^2 + 1}.</math> This means <math style="vertical-align: 0%">du = 2e^{2x}\,dx</math>. After substitution we have
+
|Use a ''u''-substitution with <math style="vertical-align: -8%">u = e^{2x}+1.</math> This means <math style="vertical-align: 0%">du = 2e^{2x}\,dx</math>. After substitution we have
 
::<math>\int \frac{2e^{2x}}{e^{2x} + 1}\, dx\,=\, \int \frac{1}{u}\,du.</math>
 
::<math>\int \frac{2e^{2x}}{e^{2x} + 1}\, dx\,=\, \int \frac{1}{u}\,du.</math>
 
|}
 
|}
Line 32: Line 32:
 
|-
 
|-
 
|
 
|
::<math>\int\frac{1}{u}\,du\,=\, \log(u).</math>
+
::<math>\int\frac{1}{u}\,du\,=\, \ln(u).</math>
 
|}
 
|}
  
Line 38: Line 38:
 
!Step 3: &nbsp;
 
!Step 3: &nbsp;
 
|-
 
|-
| Now we need to substitute back into our original variables using our original substitution <math style="vertical-align: -5%">u = e^{x^2 + 1}</math>
+
| Now we need to substitute back into our original variables using our original substitution <math style="vertical-align: -8%">u = e^{2x} + 1</math>
 
|-
 
|-
| to find&nbsp; <math>\log(u) = \log(e^{x^2 + 1}).</math>
+
| to find&nbsp; <math style="vertical-align: -20%">\ln(u) = \ln(e^{2x} + 1).</math>
 
|}
 
|}
  
Line 46: Line 46:
 
!Step 4: &nbsp;
 
!Step 4: &nbsp;
 
|-
 
|-
|Since this integral is an indefinite integral we have to remember to add a constant&thinsp; <math style="vertical-align: 0%">C</math> at the end.
+
|Since this integral is an indefinite integral we have to remember to add a constant&thinsp; <math style="vertical-align: 1%">C</math> at the end.
 
|}
 
|}
  
Line 53: Line 53:
 
|-
 
|-
 
|
 
|
::<math>\int \frac{2e^{2x}}{e^2x + 1}\, dx \,=\, \log(e^{x^2 + 1}) + C.</math>
+
::<math>\int \frac{2e^{2x}}{e^{2x} + 1}\, dx \,=\, \ln(e^{2x}+1) + C.</math>
 
|}
 
|}
  
 
[[022_Exam_2_Sample_B|'''<u>Return to Sample Exam</u>''']]
 
[[022_Exam_2_Sample_B|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 12:01, 18 May 2015

Find the antiderivative of

Foundations:  
This problem requires two rules of integration. In particular, you need
Integration by substitution (u - sub): If   is a differentiable functions whose range is in the domain of , then
We also need the derivative of the natural log since we will recover natural log from integration:

 Solution:

Step 1:  
Use a u-substitution with This means . After substitution we have
Step 2:  
We can now take the integral remembering the special rule:
Step 3:  
Now we need to substitute back into our original variables using our original substitution
to find 
Step 4:  
Since this integral is an indefinite integral we have to remember to add a constant  at the end.
Final Answer:  

Return to Sample Exam